Role of dispersion time on the properties of enzymatic-treated bamboo cellulose nanofibers. (31st August 2018) - Sri Aprilia, N A; Asniza, M; Owolabi, F A T; Rizal, Samsul; Syakir, M I; Paridah, M T; Uthaya Kumar, U Seeta; Nasrullah, R C L; Haafiz, M K; Abdul Khalil, H P S
Abstract: Cellulose nanofibers (CNF) were isolated from enzymatic treated bamboo fibers via mechanical homogenization. The effects of dispersion time (20, 30 and 40 min) by high shear homogenizer on the physicochemical properties of CNF was examined in this study. Morphological, chemical, crystallinity and thermal properties of CNF were thoroughly investigated by transmission electron microscopy (TEM), Fourier Transform Infrared spectroscopy (FT-IR), x-ray diffraction (XRD), thermogravimetry analysis (TGA) and differential scanning calorimetry (DSC), respectively. Structural analysis by FT-IR showed that chemical composition of CNF remains unchanged with the dispersion time. Yield, and nanofibrillation rate and crystallinity index of the CNF were increased with increasing dispersion time from 20 to 40 min. CNF 40 was found to be the finest which possessed diameter of 15.75 nm. Moreover, thermal stability of CNF also improved when dispersion time increased, in which CNF20, CNF30 and CNF40 exhibited Tmax. of 365.91 °C, 368.45 °C and 370.96 °C, respectively.